Electrochemical DNA Sensor for Sensitive BRCA1 Detection Based on DNA Tetrahedral-Structured Probe and Poly-Adenine Mediated Gold Nanoparticles - Dezhi Feng; Jing Su; Guifang He; Yi Xu; Chenguang Wang; Mengmeng Zheng; Qiuling Qian; Xianqiang Mi (Biosensors, 2020)
BRCA1 is the biomarker for the early diagnosis of breast cancer. Detection of BRCA1 has great significance for the genetic analysis, early diagnosis and clinical treatment of breast cancer. In this work, we developed a simple electrochemical DNA sensor based on a DNA tetrahedral-structured probe (TSP) and poly-adenine (polyA) mediated gold nanoparticles (AuNPs) for the sensitive detection of BRCA1. A thiol-modified TSP was used as the scaffold on the surface of the screen-printed AuNPs electrode. The capture DNA (TSP) and reporter DNA were hybridized to the target DNA (BRCA1), respectively, to form the typical sandwich system. The nanocomposites of reporter DNA (polyA at the 5′ end) combined with AuNPs were employed for signal amplification which can capture multiple enzymes by the specificity between biotin and streptavidin. Measurements were completed in the electrochemical workstation by cyclic voltammetry and amperometry and we obtained the low limit of detection of 0.1 fM with the linear range from 1 fM to 1 nM. High sensitivity and good specificity of the proposed electrochemical DNA sensor showed potential applications in clinical early diagnosis for breast cancer.